HYDROCHEMICAL STUDIES OF GROUNDWATER IN PARTS OF LAGOS, SOUTHWESTERN NIGERIA - AKOTEYON, ISAIAH S. (Bulletin of Geography. Physical Geography Series, 2013)
Groundwater samples were randomly collected from forty-five protected dug wells and thirteen boreholes in parts of Lagos, Southwestern Nigeria. Samples were analysed for pH, electrical conductivity and total dissolved solids in situ. Cations (calcium, magnesium, potassium and sodium) and anions (chloride, bicarbonate, sulphate and carbonates) were determined in the laboratory after standard procedure. The study is aimed at examining the extent of groundwater pollution and its possible sources using multivariate and graphical techniques. Rockware software was used to characterize groundwater composition while the sample locations were mapped with ArcMap 9.3 software. The results show high mean value in the groundwater characteristics of the protected dug wells compared to the boreholes. A significant relationship exists among EC/ TDS and major ions indicating the influence of sea water on the groundwater quality. The dominant cations and anions are in the order of: Ca2+ > Mg2+ >Na+ > K+; and Cl- >HCO3 - > SO4 2+ respectively. Factor analysis extracted two major sources of pollution (sea water and industrial) responsible for the processes controlling groundwater quality in the area. The Piper plot revealed seven distinct water types including Ca-HCO3, Ca-Cl, Mg-HCO3, Na-SO4, Mg-Cl, Na-HCO3 and Na-Cl representing 44.8%, 25%, 15.5%, 5.2%, 3.4%, 3.4%, and 1.7% respectively. The paper recommended monitoring of groundwater abstraction and treatment of industrial effluent before being released into the subsurface to prevent salinization and quality deterioration in the study area.